NHC-catalyzed cleavage of vicinal diketones and triketones followed by insertion of enones and ynones - Takaki, Ken; Hino, Makoto; Ohno, Akira; Komeyama, Kimihiro; Yoshida, Hiroto; Fukuoka, Hiroshi (Beilstein Journal of Organic Chemistry, 2017)
Thiazolium carbene-catalyzed reactions of 1,2-diketones and 1,2,3-triketones with enones and ynones have been investigated. The diketones gave α,β-double acylation products via unique Breslow intermediates isolable as acid salts, whereas the triketones formed stable adducts with the NHC instead of the coupling products.
Keywords: Breslow intermediate; N-heterocyclic carbene; ring enlargement; Stetter reaction; vicinal polyketone